2016
DOI: 10.1016/j.msea.2016.08.098
|View full text |Cite
|
Sign up to set email alerts
|

Structural, physical and mechanical properties of Ti3(Al1−xSix)C2 solid solution with x=0–1

Abstract: A series of high-purity Ti 3 (Al 1-x Si x)C 2 solid solutions with 0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 57 publications
(64 reference statements)
3
47
2
Order By: Relevance
“…During the sintering process of Ti 2 AlC, it is difficult to avoid the Ti 3 AlC 2 phase in reality, the formation of Ti 2 AlC or Ti 3 AlC 2 in the Ti‐Al‐C/TiC system has been extensively studied, similar situations were demonstrated in references and . In Ti‐Al‐C/TiC system, the existence of liquid phases promoted the growth of Ti 2 AlC . Ti‐Al liquid phases were formed firstly at temperatures around the melting point of Al, as described by reaction .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the sintering process of Ti 2 AlC, it is difficult to avoid the Ti 3 AlC 2 phase in reality, the formation of Ti 2 AlC or Ti 3 AlC 2 in the Ti‐Al‐C/TiC system has been extensively studied, similar situations were demonstrated in references and . In Ti‐Al‐C/TiC system, the existence of liquid phases promoted the growth of Ti 2 AlC . Ti‐Al liquid phases were formed firstly at temperatures around the melting point of Al, as described by reaction .…”
Section: Resultsmentioning
confidence: 99%
“…Observing that as Sn content increases in Ti 2 Al 1− x Sn x C solid solution, the lattice parameter a increases slowly and locates between that of Ti 2 AlC and Ti 2 SnC, meanwhile, the value of lattice parameter c is basically stable after the addition of tin is 0.5 mole. The behavior is similar to that of Ti 3 Al(Sn)C 2 in previous studies, but is different from that of Ti 3 Al(Si)C 2 , the lattice parameter a in Ti 3 Al(Si)C 2 shows nearly no changes while the lattice parameter c decreases linearly with increasing Si content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a significant result that indicates that one cannot glean trends for possible doping strategies by simply looking into the types of interactions that occur between A-type species in bulk binary crystal systems. The almost ideality of Al-Si interactions is supported by the recent synthesis of Ti2(Al,Si)C over the entire composition range [20]. A more detailed analysis of the electronic structure of this system close to the Fermi level would be necessary to elucidate the nature of the (lack of) chemical interactions within the A layer in this system, but this is beyond the scope of this work.…”
Section: Random Mixing Energies In Timentioning
confidence: 96%
“…Yu et al [19] investigated Cr 2 (Al,Si)C solid solutions and concluded that partial substitution of Al for Si had positive effects on the strength of the material. Gao et al [20] recently investigated solid solutions in the Ti 3 (Al 1−x Si x )C 2 system and found not only stable solid solutions through the entire composition range but also significant solid-solution hardening without compromising oxidation resistance. Finally, Horlait et al [16] provided the first evidence for Bi-containing MAX phases (Zr 2 Al 1−x Bi x C with x ∼ 0.58), while Lapauw recently reported the synthesis of Zr 2 AlC, albeit in a two-phase microstructure with ZrC being the secondary phase [21].…”
Section: Introductionmentioning
confidence: 99%